Réponse:
[tex]a. \frac{ {10}^{8} }{ {10}^{4} } = {10}^{8 - 4} \\ = {10}^{4} [/tex]
[tex]b. \frac{ {10}^{5} }{ {10}^{ - 4} } = {10}^{5 - ( - 4)} \\ = {10}^{5 + 4} \\ = {10}^{9} [/tex]
[tex]c. \frac{ {10}^{ - 7} }{ {10}^{ - 2} } = {10}^{ - 7 - ( - 2)} \\ = {10}^{ - 7 + 2} \\ = {10}^{ - 5} [/tex]
[tex]d. \frac{ {10}^{ - 3} }{ {10}^{9} } = {10}^{ - 3 - 9} \\ = {10}^{ - 12} [/tex]
[tex]e. \frac{10}{ {10}^{ - 2} } = {10}^{1 - ( - 2)} \\ = {10}^{1 + 2} \\ = {10}^{3} [/tex]
[tex]f. \frac{ {10}^{3} }{ {10}^{3} } = 1[/tex]
[tex]g. \frac{ {10}^{ - 3} }{ {10}^{3} } = {10}^{ - 3 - 3} \\ = {10}^{ - 6} [/tex]
[tex]h. \frac{ {10}^{ - 5} }{ {10}^{ - 3} } = {10}^{ - 5 - ( - 3)} \\ = {10}^{ - 5 + 3} \\ = {10}^{ - 2} [/tex]
Et voilà j'espère t'avoir aidé bon courage